Role of Salivary Tumor Necrosis Factor-alpha and Immunoglobulin- A in Recurrent Aphthous Stomatitis - Al-Ghurabei, Batool H (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Until today, the etiology of recurrent aphthous stomatitis (RAS) remains unknown, although hints of its etiologic basis lay on genetic susceptibility, infectious agents and alterations in immune mechanics.Objectives: The aim of this study was to investigate the possible alterations in salivary tumor necrosis factor-alpha (TNF-α) and Immunoglobulin-A (IgA) level in patients with RAS and its relation with clinical types of disease.Subjects and Methods: Salivary TNF-α levels were investigated in 50 RAS patients and 25 healthy controls by enzyme-linked immunosorbent assay (ELISA). Single radial immune diffusion method was used for estimation of IgA level in two studied groups.Results: Salivary level of TNF-α was significantly higher in RAS patients than in healthy controls (p